Sports Corruption and Legal Accountability: A Case Study of Corruption in Indonesian Football and Its Impact on Justice (Indonesian Sports Justice Review, 2025)
Corruption remains a significant issue in Indonesian sports, particularly in football, where match-fixing, bribery, and financial mismanagement continue to undermine the integrity of the sport. This paper investigates the prevalence of corruption in Indonesian football and its legal and social consequences. By analyzing high-profile corruption scandals, the study examines how corruption impacts justice within the sport, from player exploitation to fan disillusionment. It evaluates the effectiveness of current legal frameworks and enforcement mechanisms in addressing corruption, and looks at the role of sports organizations, government bodies, and law enforcement in promoting accountability. The paper concludes with recommendations for legal reforms, improved transparency, and stronger institutional oversight to ensure fairness and integrity in Indonesian football.